Functional characterization of two paralogs that are novel RNA binding proteins influencing mitochondrial transcripts of Trypanosoma brucei - Kafková, Lucie; Ammerman, Michelle L; Faktorová, Drahomíra; Fisk, John C; Zimmer, Sara L; Sobotka, Roman; Read, Laurie K; Lukes, Julius; Hashimi, Hassan (RNA (New York, N.Y.), 2012)
A majority of Trypanosoma brucei proteins have unknown functions, a consequence of its independent evolutionary history within the order Kinetoplastida that allowed for the emergence of several unique biological properties. Among these is RNA editing, needed for expression of mitochondrial-encoded genes. The recently discovered mitochondrial RNA binding complex 1 (MRB1) is composed of proteins with several functions in processing organellar RNA. We characterize two MRB1 subunits, referred to herein as MRB8170 and MRB4160, which are paralogs arisen from a large chromosome duplication occurring only in T. brucei. As with many other MRB1 proteins, both have no recognizable domains, motifs, or orthologs outside the order. We show that they are both novel RNA binding proteins, possibly representing a new class of these proteins. They associate with a similar subset of MRB1 subunits but not directly with each other. We generated cell lines that either individually or simultaneously target the mRNAs encoding both proteins using RNAi. Their dual silencing results in a differential effect on moderately and pan-edited RNAs, suggesting a possible functional separation of the two proteins. Cell growth persists upon RNAi silencing of each protein individually in contrast to the dual knockdown. Yet, their apparent redundancy in terms of cell viability is at odds with the finding that only one of these knockdowns results in the general degradation of pan-edited RNAs. While MRB8170 and MRB4160 share a considerable degree of conservation, our results suggest that their recent sequence divergence has led to them influencing mitochondrial mRNAs to differing degrees.
Keywords: biologické modely; protozoální proteiny; sekvenční homologie; Substrate Specificity; podjednotky proteinů; vazba proteinů; proteiny vázající RNA; Protozoan Proteins; Models, Biological; RNA; messenger RNA; Sequence Homology; RNA, Messenger; RNA, Mitochondrial; Macromolecular Substances; Trypanosoma brucei brucei; Cloning, Molecular; konzervovaná sekvence; Protein Subunits; RNA mitochondriální; RNA-Binding Proteins; makromolekulární látky; klonování DNA; substrátová specifita; Protein Binding; Conserved Sequence